Dwifungsi Gaya Baru? Penempatan Prajurit Aktif di Jabatan Sipil dalam Revisi UU TNI 2025 dan Dampaknya terhadap Demokrasi - Suif Al-Adawiyah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The revision of Law No. 34 of 2004 concerning the Indonesian National Armed Forces (TNI Law) on March 20, 2025, particularly regarding the expanded placement of active military personnel in civilian positions, has sparked concerns about the return of Dwifungsi ABRI. This study critically analyzes whether this expanded role can be categorized as a New Style Dwifungsi and its implications for democratic consolidation in Indonesia. Employing a qualitative descriptive approach with a literature review, this research examines the historical roots of Dwifungsi ABRI, the crucial changes in the 2025 TNI Law revision, and analyzes the concerns of civil society and academics. The findings indicate the potential weakening of civilian supremacy, a decline in military professionalism, and accountability issues. International comparative studies underscore the importance of civilian supremacy and military neutrality in a democracy. The conclusion emphasizes the necessity of upholding democratic integrity and civilian supremacy through transparency and strict accountability in any military placement within the civilian sphere.